Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Produktifitas Kerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Tangerang Gas Industri - Suryadi; Andiana Rosid; Ika Chindy Pebiawati (Universitas Muhammadiyah Metro, 2024)
Based on the data increasing human productivity in the company is not only related to the problem of scheduling work and skills in completing work but also regarding the conditions and atmosphere of work and work relationships that exist among co-workers. At PT. Tangerang Gas Industri certainly needs employees who are productive at work because it is a company in the fields of pre-commissioning, Gas Service, Trading and Industrial Suppliers. Employee productivity depends on individual work productivity, thus depending on each individual in carrying out their work. This study has a goal, namely to find out whether there is an influence between compensation on employee job satisfaction. To determine whether there is influence of the work environment on employee job satisfaction. To find out whether there is an effect of compensation on employee work productivity. To determine whether there is influence of the work environment on employee productivity. To find out whether there is an influence between job satisfaction on employee work productivity. The sample of this research are employees of PT. Tangerang Gas Industry with 36 employees. Data collection used a questionnaire, and data analysis used a Validity Test, Reliability Test, Normality Test, Homogeneity Test, Linearity Test and Regression Significance and Path 2 Substructural Analysis with the program (SPSS 20). The results showed that there was a direct effect of compensation and work environment on employee productivity, there was a direct effect of compensation and work environment on job satisfaction, and there was a direct effect of job satisfaction on employee productivity.